Impact of extended social isolation on spontaneous play in childhood - Souza, Andrielle Sisneiro de; Truccolo, Adriana Barni (Seven Editora, 2023)
The coronavirus pandemic led to the interruption of school's routine and the social isolation and confinement of thousands of children revealing different childhoods in different contexts and cultures, bringing out vulnerabilities and impacting the child's cognitive, social and emotional development. In view of this scenario, the objective was to understand the influence of extended social isolation on the frequency of children's participation in active play. Research with a cross-sectional quantitative approach, carried out in six municipal public schools of Alegrete with 164 children, 76 girls and 188 boys with twelve years of age. Data were collected via electronic form, and the descriptive analysis of qualitative variables was organized in tables of specific frequencies. The project was approved by the ethics committee with registration CAAEE44380221.8.0000.8091. The results showed that 46.3% of the children played computer games every day, 45.7% practiced some sport or dance, and 40% played outdoors. It is concluded that isolation brought profound changes in children's routine, affecting not only studies, but practically all aspects of their lives. DOI:https://doi.org/10.56238/emerrelcovid19-024